Type II Vitamin D Dependent Rickets: A Case Report - Malla, Kalpana K; Malla, Tejesh; Shaw, Chandan; Thapalial, Anna (Journal of Nepal Paediatric Society, 2009)
Vitamin D-dependent rickets Type II is a rare autosomal recessive disorder. Alopecia of the scalp or the body is seen in some families with Vitamin D-dependent rickets Type II. We report a child with this disease, and review the salient features of this disease with emphasis on the associated alopecia. Due to lack of facilities for estimation of 1, 25(OH)2 D and parathyroid hormone, alopecia remains the only clue to the diagnosis of this rare syndrome in association with resistant rickets. Key words: Rickets, Vitamin D metabolism DOI: 10.3126/jnps.v30i1.2460 Journal of Nepal Paediatric Society Vol.30(1) 2010 46-49